ANALISIS ASAM LEMAK BEBAS DAN KADAR AIR MENGGUNAKAN ADSORBEN KUNYIT DENGAN PENGARUH LAMA WAKTU ADSORPSI - Linda Duwi Febriyanti; Vika Ayu Devianti; Intan Puspitasari (Jurnal Kesehatan Yamasi Makassar, 2024)
Cooking oil is one of the daily necessities for people. Repeated use of cooking oil can pose health risks due to the presence of potentially harmful compounds. The quality of cooking oil can be assessed based on its free fatty acid level and moisture content, with SNI 7709:2019 setting maximum standards of 0,3% for free fatty acid level and 0,1% for moisture content. Therefore, there is a need to reduce the levels of free fatty acid and moisture content in used cooking oil. One of the methods that can be used is adsorption using turmeric powder as adsorbent. The research aims to investigate how varying adoption times affect moisture content and free fatty acid levels in used cooking oil. The results indicate that turmeric is capable of reducing the free fatty acids and moisture content in used cooking oil. This study reveals that the free fatty acid decreases with increasing adsorption time of 35, 45, 50, 55, and 60 minutes, yielding values 0,881; 0,794; 0,706; 0,618; and 0,559%, respectively. The moisture content results with adsorption times of 35, 45, 50, dan 55 minutes were 0,120; 0,101; 0,095, and 0,080 %, respectively. The optimal reduction in free fatty acids occurs at 60 minutes of adsorption, with a decrease of 45,08%. The best reduction in moisture content is achieved at 55 minutes of adsorption, with a decrease of 40,74%.